2022
DOI: 10.1080/17482631.2022.2099023
|View full text |Cite
|
Sign up to set email alerts
|

The ways specialist nursing students understand the work in the ambulance service - a national Swedish phenomenographic study

Abstract: Objective To explore and describe the ways specialist ambulance nursing (SAN) students understand the work in the ambulance service. Design, sample, and measurements An explorative descriptive design was carried out through individual interviews with 16 SAN students from all parts of Sweden and analysed in accordance with the phenomenographic tradition. Findings Five different ways of understanding the work were described and each was assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the present study, the distribution in the participating region was 78.5% specialist trained nurses (dominated by SANs), 15.5% RNs, and 6% EMTs. The total number of employed ACs was 148 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the distribution in the participating region was 78.5% specialist trained nurses (dominated by SANs), 15.5% RNs, and 6% EMTs. The total number of employed ACs was 148 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further to the above, some studies were identified in the domain of nursing education. A phenomenographic study examined the ways that specialist ambulance nursing students understood their work in the Swedish Ambulance Service (Wallin et al, 2022).…”
Section: Some Appli C Ati On S Of Phenomenog R Aphy In Nur S Ingmentioning
confidence: 99%
“…The authors uncovered five different ways of understanding work: medical, practical, patient-oriented, commanding and comprehensive roles (Wallin et al, 2022). These diverse descriptions can offer support to curriculum design and development of expertise.…”
Section: Some Appli C Ati On S Of Phenomenog R Aphy In Nur S Ingmentioning
confidence: 99%
See 2 more Smart Citations